THE INFLUENCE OF KNOWLEDGE AND RELIGIOSITY ON ZIS DIGITAL PAYMENTS WITH EASE OF ACCESS TO TECHNOLOGY AS A MODERATING VARIABLE - Mia Amelia; Nasrulloh (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
The purpose of this study is to evaluate the level of knowledge and religiosity towards ZIS digital payments through the BAZNAS platform among students. The population in this study is students of the Faculty of Islam, Trunojoyo Madura University, with a minimum sample of 91 respondents selected using random sampling techniques. This research method uses a quantitative method with an analysis technique using the Structural Equation Model (SEM)-Partial Least Square (PLS), which goes through 3 stages, namely: Outer Mode Analysis, Inner Model, and Hypothesis Testing. The results of the study show that knowledge has a significant effect on digital payments, while religiosity has no significant effect on digital payments, ease of technology has a significant effect on digital payments, ease of technology cannot moderate knowledge of digital payments, and ease of technology cannot moderate religiosity towards digital payments. In conclusion, to increase ZIS digital payments among students, it is necessary to increase knowledge and religiosity as the main foundation. The ease of technology is also a significant supporting factor, to ensure that the ZIS digital payment process is more practical and easily accessible.